A Blue Ocean Strategy for Herbal Liniment: Escaping Tight Competition in Indonesian Market - Yohana Santoso, Elvina; Murhadi, Werner (Faculty of Economics and Business Udayana University, 2023)
The herbal liniment industry operates in a highly competitive and saturated market. This study focuses on developing a blue ocean strategy for Yodosan Herba Natur, an herbal liniment manufacturer, to treat musculoskeletal pain. Through qualitative interviews with 17 participants in Surabaya, customer preferences and latent needs for musculoskeletal pain treatment were explored. Data analysis revealed seven main themes: effectiveness, experience, ease of use, sensation, availability, recommendation, and other factors. This research assessed the competitive landscape comprehensively using blue ocean strategy analysis tools. The blue ocean strategy is to develop an odorless product with long-lasting heat, a strong brand image, widespread availability, compact size, and affordable prices. New factors introduced are packaging designs, niche marketing, and strategic partnerships. The findings highlight the potential for Yodosan Herba Natur to revolutionize musculoskeletal pain treatment and capture the untapped markets of second and third-tier non-consumers.